Influence of total genomic alteration and chromosomal fragmentation on response to a combination of azacitidine and lenalidomide in a cohort of patients with very high risk MDS. Issue 10 (October 2015) - Ganster, Christina; Shirneshan, Katayoon; Salinas-Riester, Gabriela; Braulke, Friederike; Schanz, Julie; Platzbecker, Uwe; Haase, Detlef
Highlights Molecular karyotyping improves stratification of very high risk MDS/AML patients. Patients treated by a combination of azacitidine and lenalidomide were analyzed. The size of total genomic aberrations was a predictive marker for overall survival. Heavily rearranged chromosomes were associated with molecular TP53 mutations. The occurrence of both markers together was associated with therapy refractoriness.